Combined Loop-Mediated Isothermal Amplification Assays for Rapid Detection and One-Step Differentiation of Campylobacter jejuni and Campylobacter coli in Meat Products - Kreitlow, Antonia; Becker, André; Ahmed, Marwa F. E.; Kittler, Sophie; Schotte, Ulrich; Plötz, Madeleine; Abdulmawjood, Amir (Frontiers in Microbiology, 2021)
A loop-mediated isothermal amplification (LAMP) assay system was established, allowing rplD gene-based simultaneous detection of Campylobacter jejuni and Campylobacter coli in enriched meat products. Additionally, one-step differentiation of target species on agar plates was enabled by cdtC gene- and gyrA gene-based duplex LAMP. Both the rplD and cdtC-gyrA LAMP assay amplified the target sequences in all 62 C. jejuni and 27 C. coli strains used for determining inclusivity and revealed 100% exclusivity towards 86 tested non-target species. Throughout the entire experiments, C. jejuni and C. coli strains were 100% distinguishable by melting curves of cdtC and gyrA LAMP products. After 24-h enrichment, the rplD LAMP assay reliably detected 10–100 CFU/g in artificially contaminated minced meat. Investigation of naturally contaminated meat samples revealed a diagnostic accuracy of 95% towards real-time PCR and 94.1% towards the standard culture method applying the 24-h incubation period. Diagnostic sensitivity and specificity, positive and negative predictive values were 89.8%, 100%, 100% and 91.2% when measured against real-time PCR, and 89.6%, 98.1%, 97.7% and 91.2% when measured against the standard culture method, respectively. After 48-h enrichment, the detection limit of the rplD LAMP assay improved to 1–10 CFU/g in artificially contaminated minced meat. Applying the 48-h incubation period on naturally contaminated meat samples resulted in 100% concordant results between rplD LAMP, real-time PCR and the standard culture method. The established LAMP assay system was proved to be suitable for rapid meat sample screening. Furthermore, it constitutes a promising tool for investigating other Campylobacter sources and could therefore make a valuable contribution to protect consumers from foodborne illness.